2017
DOI: 10.4236/jbbs.2017.78026
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Blue LED Light on Behavior and Retinal Function in Maternal and Offspring Mice

Abstract: In the present study, we investigated whether blue light emission diode (LED) light exposure affects the maternal behavior of mice. The brain function of the offspring mice, including short-term memory, locomotor activity, anxiety-like behavior, and depression-like behavior, was evaluated. Pregnant mice at day 11 were housed in the apparatus for exposure to blue LED light during the daytime. Nesting behavior and the survival of pups were observed until weaning. After weaning, the offspring mice were bred in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, one study reported that C57BL/6 mice exposed to either bLAD or CWF showed no behavioral differences when performing in Y-maze test, object recognition test, tail suspension test, and open field test. 12 In the present study and in a few previously mentioned studies, 12,19 no major differences were seen in behavior between lighting conditions. Other behavioral tests could be affected by lighting, especially in melatonin producing strains of mice.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Furthermore, one study reported that C57BL/6 mice exposed to either bLAD or CWF showed no behavioral differences when performing in Y-maze test, object recognition test, tail suspension test, and open field test. 12 In the present study and in a few previously mentioned studies, 12,19 no major differences were seen in behavior between lighting conditions. Other behavioral tests could be affected by lighting, especially in melatonin producing strains of mice.…”
Section: Discussionsupporting
confidence: 60%
“…This finding is consistent with a previous study that investigated nesting as a measure of maternal behavior in ICR mice. 19 That study also found no significant difference found in nest type between bLAD and fluorescent lighting. 19 Furthermore, in the current study, BALB/c male and female mice housed under CWF conditions made dome type nests in numbers that were approximately equal to that of bowl type nests, which were the dominant type of nest built by the other 2 strains.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Sensitiveness to illumination may have developed as a defensive mechanism to detect potential predators approaching from above ( Wei et al., 2015 ). Moreover, mice were shown to possess photoreceptors sensitive to blue light ( Horibe et al., 2017 ; Peirson et al., 2018 ; Vicente-Tejedor et al., 2018 ). Several authors called attention in the design and interpretation of optogenetic behavioral experiments, taking into account possible artefacts caused by light leakage in the light delivery pathway ( Ung and Arenkiel, 2012 ; Allen et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%